Patologie organizacyjne w szkolnictwie wyższym w Polsce w latach 2008-2011 dotyczące organizacji procesu dydaktycznego i funkcjonowania uczelni oraz związane z kadrą nauczycielską szkół wyższych = Organisational pathologies in higher education in Poland in 2008-2011 related to the organisation of the didactic process and the functioning of higher education institutions, as well as pathologies related to higher education teaching staff - Stachowicz, Jacek (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents organisational pathologies occurring in Polish higher education in 2008-2011, focusing specifically on pathologies concerning the organisation of the didactic process and functioning of HEIs, as well as pathologies related to teaching staff in HEIs. The research is a continuation of a larger study, covering the years 2002-2004 and 2005-2007. The research method used is document analysis.
Keywords: higher education; organisational pathologies; quality of education; Polish Accreditation Committee; szkolnictwo wyższe; patologie organizacyjne; jakość kształcenia; Polska Komisja Akredytacyjna